Effect of Dolutegravir regimen against other regimens on some hematological parameters, CD4 count and viral load of people living with HIV infection in South Eastern Nigeria - Echefu, Stella N.; Udosen, Joseph E.; Akwiwu, Euphoria C.; Akpotuzor, Josephine O.; Obeagu, Emmanuel Ifeanyi (Medicine (Baltimore), 2023)
Background: Appropriate usage of highly active antiretroviral therapy (HAART) suppresses human immunodeficiency virus (HIV) replication. One of such HAART is dolutegravir (DTG) containing regimen which Nigeria included in her national protocol, as the preferred first-line option, with particularly fixed dose combination of tenofovir/lamivudine/dolutegravir (TLD) in 2018. Aim: To access the impact of this regimen as against other regimens on some hematological parameters as well as cluster of differentiation 4 (CD4) count and viral load on people living with HIV infection Methods: The study site is a health facility center supported by President Emergency Plan for acquired immunodeficiency syndrome (AIDS) Relief where people living with HIV infection (PLWHIV) visit for their routine management in Abakaliki, Ebonyi State. A hundred and twenty-two (122) subjects participated, 58 PLWHIV and 64 control subjects. CD4 + count by partec cyflow auto analyzer, while the Viral load assay was by Roche COBAS Ampriplep/COBAS TaqMan molecular systems. Full blood count determination was by Sysmex XE-2100 hematology auto analyzer, while the detection of antibody to HAART was by Petz and direct Coombs tests. Results: Mean values of hemoglobin (Hb), Total white cell count, Lymphocytes, Monocytes and CD4 + counts of people living with HIV infection (PLWHIV) were significantly (P = .0001) lower than the control subjects. The Hb level of PLWHIV on Efavirenz combination (TDF/3TC/EFV) are comparable 123 ± 32g/l with those on Ritonavir combination (TDF/3TC/LPV/R) 136 ± 16g/l and Dolutegravir (TLD)134 ± 20.0g/l (P = .307). On the other hand, total white cell count (4.55 ± 1.99 × 109/L) of those on Efavirenz combination (TDF/3TC/EFV) and Dolutegravir (TLD) (4.53 ± 1.31 × 109/L) were significantly higher than those on Ritonavir combination (TDF/3TC/LPV/R) (4.09 ± 1.15 × 109/L). The Viral Load of PLWHIV on Dolutegravir (TLD) was significantly lower 171.57 ± 4.56 copies/mL than those on Efavirenz combination (TDF/3TC/EFV) (86,395.91 ± 27,476.57copies/mL) and Ritonavir combination (TDF/3TC/LPV/R) (81,188.83 ± 13,393.47 copies/mL), respectively. Conclusion: Some hematological parameters (such as Hb, total white cell counts and CD4 + count) were lower in people living with HIV than values seen in control group. The 3 regimens used in the management of HIV infection in the locality revealed comparable Packed cell volume and Hemoglobin levels. Total white cell count of those on Efavirenz and DTG is comparable with higher values than those on Ritonavir.